2017
DOI: 10.1002/2017gl075258
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Disposal and the Earthquake Sequences During 2016 Near Fairview, Pawnee, and Cushing, Oklahoma

Abstract: Each of the three earthquake sequences in Oklahoma in 2016—Fairview, Pawnee, and Cushing—appears to have been induced by high‐volume wastewater disposal within 10 km. The Fairview M5.1 main shock was part of a 2 year sequence of more than 150 events of M3, or greater; the main shock accounted for about half of the total moment. The foreshocks and aftershocks of the M5.8 Pawnee earthquake were too small and too few to contribute significantly to the cumulative moment; instead, nearly all of the moment induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 35 publications
3
50
0
Order By: Relevance
“…The 3 September 2016 12:02:44 (UTC) M 5.8 earthquake near Pawnee, Oklahoma, ruptured the previously unmapped, northwest‐striking Sooner Lake fault and was the largest historically recorded earthquake in the state, exposing more than 70 k people to strong ground shaking, and causing light damage to structures in the vicinity (Clayton et al, ; U.S. Geological Survey PAGER, 2018; Yeck et al, ; Figure ). Numerous studies point to the injection of produced wastewater associated with oil and gas operations as a critical causative factor for the earthquake (e.g., Chen et al, ; McGarr & Barbour, ; Yeck et al, ). The earthquake is part of an unprecedented increase in seismicity rates in Oklahoma of more than two orders of magnitude compared to historical rates, owing to induced earthquakes (Ellsworth, ; Keranen et al, ; Llenos & Michael, ; Moschetti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The 3 September 2016 12:02:44 (UTC) M 5.8 earthquake near Pawnee, Oklahoma, ruptured the previously unmapped, northwest‐striking Sooner Lake fault and was the largest historically recorded earthquake in the state, exposing more than 70 k people to strong ground shaking, and causing light damage to structures in the vicinity (Clayton et al, ; U.S. Geological Survey PAGER, 2018; Yeck et al, ; Figure ). Numerous studies point to the injection of produced wastewater associated with oil and gas operations as a critical causative factor for the earthquake (e.g., Chen et al, ; McGarr & Barbour, ; Yeck et al, ). The earthquake is part of an unprecedented increase in seismicity rates in Oklahoma of more than two orders of magnitude compared to historical rates, owing to induced earthquakes (Ellsworth, ; Keranen et al, ; Llenos & Michael, ; Moschetti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the analysis conducted in McGarr and Barbour (), where they focused on the scaling between total seismic moment for the M 5 earthquake sequences in Oklahoma and injection volume within 10 km of each sequence, instead of maximum seismic moment. They reported scaling factor between 1 and 30 GPa and suggested that such variations maybe attributed to heterogeneity in shear modulus.…”
Section: Discussionmentioning
confidence: 53%
“…They reported scaling factor between 1 and 30 GPa and suggested that such variations maybe attributed to heterogeneity in shear modulus. The average scaling factor between M0 and Δ V for the sequence here is about 13.5 GPa if assuming the relationship in McGarr () and McGarr and Barbour () or 27 GPa if assuming the relationship in McGarr (). The former suggests that the scaling factor is well within the range reported in McGarr and Barbour () and could be attributed to heterogeneity, while the latter suggests a possible role of elastic stress transfer with stress perturbations in the deviatoric stress field (McGarr, ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(right) Monthly injection volumes from all injection wells within 10 km of the monitoring well (highlighted in the map), in cubic meters; data are not available prior to 2014 or after 2017. For comparison, the dashed line shows the injection history within 10 km of the Pawnee mainshock (McGarr & Barbour, ), which includes a few wells in Osage County (Barbour et al, ); this ends abruptly because active wells were shut in following the mainshock.…”
Section: Discussionmentioning
confidence: 99%